Differential grain filling in apical and basal spikelets of compact panicle rice is associated with difference in expression of miRNAs targeting gene products involved in grain filling - Chandra, T; Shaw, B P (ORYZA-An International Journal of Rice, 2020)
Development of rice cultivars bearing numerous spikelets by breeding approach to increase production of the crop to feed the ever increasing human population accompanies poor filling of grains in their basal spikelets preventing achievement of the yield potential. To understand the reason of such poor grain filling at the level of the initial biochemical events, 5 RACE library was prepared taking RNA extracted from the spikelets of two indica rice cultivars, a compact-panicle Mahalaxmi bearing numerous spikelets per panicle (>350) and a laxpanicle Upahar bearing fewer spikelets (